Introducing Scuba Diving for Fishermen of Pantai Kondang Merak, Malang - Oktiyas Muzaky Luthfi; Andi Isdianto (Universitas PGRI Semarang, 2019)
Pantai Kondang Merak has a biodiversity of marine resources, so that the community always depend on exploration and exploitation activities through fishing, and catch lobster, sea cucumber, abalone and some of algae with diving activities. The diving activities usually in 5-30 m depth in reef area, using air compressor that will danger their live. This compressor has long regulator hose (about 50 m), during diving process the hose will be tied in their waist with 5-7 kg lead, it similar with weight belt in SCUBA diving. The hose also has other function as keep the diver from water current drifting. This method will disrupt the air supply from compressor to mouth face and endanger the life of diver. The safety diving standard is using a SCUBA set, that has a portable air supply and clean air, unlike the air that resulted by the conventional compressor. The aim of this activity is to give safe diving method and give ecotourism skill to the fisherman in Kondang Merak, thus avoiding fisherman from decompression sickness and seek alternative livelihood during west monsoon.